ANALISIS KNOWLEDGE WORKER SEBAGAI KONTRIBUSI DALAM MENINGKATKAN KINERJA KARYAWAN PT. ASURANSI JIWASRAYA (PERSERO) KANTOR PUSAT - Agustina, Linda (Jurnal Ilmu Administrasi Bisnis, 2016)
PT. Asuransi Jiwasraya (Persero) head office is business unit which actively pioneering knowledge management. One of the effort is operating knowledge sharing which is one of the stages of the socialization process of knowledge creation. Knowledge management is a container for managing the knowledge possessed by the human component. The human component is worker implement the process of knowledge creation. Knowledge sharing in PT. Asuransi Jiwasraya (Persero) named JKS 48. Worker program conducting knowledge sharing been seen whether it fulfills the five criteria as knowledge workers. The fifth criteria knowledge worker is self-driven, motivated, action oriented, responsible and a team player.Methods of data collection were used interviews, participant observation, collecting documents and literature, then analyzed with case studies. The results showed that knowledge sharing implemented are good and enthusiastic worker to follow, and there is a knowledge sharing activities are also regularly carried out by the divisions, PP and PK division. There are three key informants who did not fulfill the criteria of knowledge worker, discussion of knowledge workers and knowledge sharing in accordance with the theory. 16 key informant who fulfill the criteria for knowledge workers to contribute to the performance. Recommendation to PT. Asuransi Jiwasraya (Persero) head office is supported key informants who fulfill the criteria and build a repository to collect ideas, ideas and knowledge possessed by each worker head office, regional offices and branch offices.